Diagnostic and Therapeutic Role of Spiral CT Angiography in Intracerebral Aneurysms Presenting with Acute Subarachnoid Haemorrhage - Anjum, Sadia; Rana, Saeeda; Sattar, Abdul; Jalal, Malik Liaqat Ali (Biological and Clinical Sciences Research Journal, 2025)
Subarachnoid haemorrhage (SAH), which is usually due to the rupture of the intracranial aneurysms, is a severe disease, which is a neurological emergency that requires efficient and reliable diagnosis. Computed Tomography Angiography (CTA) has proved an important non-invasive screening tool in the diagnosis of vascular abnormalities of the brain. Objective: This research was based on the diagnostic value of spiral CTA in detecting intracranial aneurysms in patients discharged with acute spontaneous subarachnoid haemorrhage. Methods: Bands of the 30 patients with non-traumatic SAH who were admitted due to presenting SAH and finally verified on emergency non-contrast CT were examined during a prospective descriptive study. Each of the patients was identified by CTA using a Toshiba Aquilion 16-isce multidetector CT scanner. Pre-contrast, as well as post-contrast images were taken, and 3D reconstructions were provided, which consist of maximum intensity projection (MIP) and volume-rendered imaging. Information on aneurysms was gathered in terms of size, shape, multiplicity, location, and findings connected to the aneurysms, i.e., vasospasm and infarction. Results: This CT angiography was able to detect intracranial aneurysms in every patient. Anterior circulation encompassed 83.3% of all the aneurysms, and the most frequent one, which occurred at the anterior communicating artery. The vast majority of aneurysms were between 3 and 7 mm. CTA was also used, which also showed related complications such as the presence of 30% and infarctions of 10%. The modality was found to be very sensitive to aneurysms that are 3 mm and upwards. Conclusion: Spiral CTA is a fast, dependable, and noninvasive imaging method with high diagnostic value in identifying intracranial aneurysms in the acute SAH. It plays a critical role in early diagnosis, treatment planning, and enhancement of patient outcomes. It can be discussed as one of the main imaging modalities used in assessing emergency neurovascular.